71 Engaging with paediatric junior doctors: building relationships and enhancing their learning and ours. (4th October 2017) - Poisson, J; Parish, EJ; Tobin, H; Sharma, S
Abstract : Background: Quaternary hospitals, like GOSH, facilitate a wealth of learning opportunities; however, work is often thought of as service provision rather than experiential learning. It was noted junior doctors (JDs) were withdrawing from interacting in wider hospital activity, non-essential education and social events, which has made engagement a significant challenge. Our project aim is to improve our understanding of the issues facing JDs through the use of focus groups. Methods: We held focus groups with JDs in their departments. We aimed to conduct 1–2 meetings a month with as many JDs available, without impacting on service needs. The meetings took place around lunchtime for an hour and lunch was provided. The format was flexible and did not require an agenda. Minutes were taken, with a note of how many JDs attended. Concerns were prioritised and immediate actions were escalated. Results: Over 12 months we held 12 focus groups with an average of 5–10 JDs at each session. Minutes were collated and themes included concerns over staffing, low morale and its impact on education and training, suitability of training posts and general paediatric training for core trainees and surgeons. JDs reported they found the meetings to be a useful opportunity to confidentially raise concerns and reflect on training. Conclusion: The use of focus groups as an engagement tool enhanced PGME's understanding of the concerns of JDs and how to improve the education and training in real-time. It has also helped to identify and share good practice. The lack of senior consultant presence helped to facilitate a confidential environment, which enabled a freedom of speech, yielding more information to shape learning events. We intend to use the feedback to improve communication and engagement with JDs, such as developing the PGME website, ensuring the PGME App is fit for purpose and providing innovative education opportunities.